Association of malondialdehyde(mda) level and renal impairment in spontaneously hypertensive rats - Wahab, Nor Akmal (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2004)
Compared to normotensives, hypertensives and patients with renal failure have higher levels of plasma malondialdehyde (MDA) and unnary 8-epi-prostaglandin F2a. The exact significance of the raised levels of :MD A and urinary 8-epi-prostaglandin F2a activity in hypertension is unclear. It is however unclear if they are involved in the pathogenesis of hypertension or are a consequence of hypertension. This study attempts to ascertain the age at which changes in blood pressure, levels of plasma 1\IDA, urinary 8-epi-prostaglandin F2a and renal impairment begin to occur in Spontaneously I-Iypertensive rats (SHR). Sixty-six, 8-week old Spontaneously Hypertensive Rats (SHR) were divided equally into eleven groups with age-matched Wistar-Kyoto rats (WKY) as controls. Every 4 weeks, blood pressure was recorded by the tail-cuff method on six SHR and six WKY rats. After the measurement of blood pressure, the rats were then individually housed in metabolic cages for collection of 24-hr urine samples for 8-epi-prostaglandin . F2a and urine electrolyte determinations and from 36 to 48 weeks onwards for the measurement of food and water intake. After the urine collection the rats were anaesthetised for measurement of glomerular filtration rate (GFR) using a standard 3Hinulin clearance protocol. Immediately upon completion of the measurement of glomerular filtration rate, the animals were exsanguinated for the determination of plasma malondialdehyde levels. Mean body weight of SHR was consistently and significantly lower than that of WKY rats from the age of 12 weeks onwards (p<O.Ol). Systolic blood pressure was significantly higher in the SHR when compared to those in age-matched WKY rats from the age of 8 weeks onwards (p<O.Ol). Plasma MDA and urinary 8-epi-prostaglandin F2a were all significantly higher in SHR when compared to the controls from the age of 16 and 12 weeks onwards respectively (p<0.05 for :MDA; p<O.Ol for 8-epi-prostaglandin F2a). GFR was significantly lower (p<0.05) in SHR from the age of 28 weeks onwards when compared with age-matched normotensive WKY rats. No significant differences were noted in plasma creatinine concentrations between the two groups throughout the study period. In conclusion, it seems, evidence for increased free radical activity appears four to six weeks after the development of hypertension in SHR rather than the cause of it. In addition, as renal impairment only becomes evident after changes in free radical activity, increased free radical activity might have a role in some of the complications associated with hypertension.